Regulatory Aspects Analysis Model Supported by Knowledge Management to Brazilian Healthtechs (Management and Connections Journal, 2026)
The objective of this research is to develop and validate a model of analysis of regulatory aspects supported by Knowledge Management applicable to Brazilian healthtechs. A bibliographic and documentary research methodology was applied, with a survey and application of multicriteria decision analysis (PAPRIKA method), with the participation of professionals specialized in the area of regulatory affairs working in the Brazilian medical products industry. The validated model has the following structure: i) 17 legislations for medical devices; ii) 18 KM processes, practices and tools and iii) Flow of steps for the regularization of healthtech, necessary certifications and actions for the regularization of the medical product. The structured model contributes to the advancement of research in innovation in the area of Health and medical products, in addition to being a guide for healthtech entrepreneurs in the country to regularize their company and medical products.
Keywords: technological innovation; knowledge management; regulatory affairs; healthtech; medical equipment & devices